2012
DOI: 10.1093/ejcts/ezs033
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-eight years' experience of arterial switch operation for transposition of the great arteries in a single institution

Abstract: ASO was performed with satisfactory results in the overall survival and functional status. PS was the main reason for re-operation. Coronary lesions can appear late without any symptoms. Benefits of ASO can be achieved by long-term follow-ups of PS, AI and coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 20 publications
8
52
3
3
Order By: Relevance
“…To this end, our study is unique in several respects, including the longest follow-up to date (median 18.7 years), 12,16,26,27 the comprehensive nature of the dataset (ie, physical examination, noninvasive imaging, hemodynamic studies, cardiopulmonary exercise testing, catheter and surgical interventions), and the arrhythmic and combined adverse cardiovascular outcomes. We deliberately restricted the study population to an early cohort (ie, with ASO between 1983 and 1999) to focus on long-term results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To this end, our study is unique in several respects, including the longest follow-up to date (median 18.7 years), 12,16,26,27 the comprehensive nature of the dataset (ie, physical examination, noninvasive imaging, hemodynamic studies, cardiopulmonary exercise testing, catheter and surgical interventions), and the arrhythmic and combined adverse cardiovascular outcomes. We deliberately restricted the study population to an early cohort (ie, with ASO between 1983 and 1999) to focus on long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most previous longitudinal studies have reported an average follow-up of ≤10 years. 12,16,26,27 To maximize completeness of data collection, the catchment area was limited to patients living in New England. Moreover, data were supplemented by directly contacting patients and by acquiring records from secondary sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations